2014
DOI: 10.1016/j.finmar.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Commodity index trading and hedging costs

Abstract: Trading by commodity index traders (CITs) has become an important aspect of financial markets over the past 10 years. We develop an equilibrium model of trader behavior that relates uninformed CIT trading to futures prices. A key implication of the model is that CIT trading reduces the cost of hedging. We test the model using a unique non-public dataset that allows us to precisely identify trader positions. We find evidence, consistent with the model, that index traders have become an important supply of price… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Applying this idea to recent developments in commodity futures markets, Brunetti and Reiffen (2011), Acharya, Lochstoer, and Ramadorai (forthcoming), Cheng, Kirilenko, and Xiong (2012), and Hamilton and Wu (forthcoming) proposed that the growing volume of commodity index investors could produce hedging price pressure on the buy side, with Hamilton and Wu (forthcoming) finding that the average compensation to the long position in oil futures contracts has decreased but become substantially more volatile since 2005. Etula (forthcoming), Acharya, Lochstoer, and Ramadorai (forthcoming), Danielsson, Shin, andZigrand (2011), andCheng, Kirilenko, andXiong (2012) have stressed the role of limited working capital on the part of potential arbitrageurs as the key factor determining how much the futures price might deviate from the expected future spot price.…”
Section: Aboutmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying this idea to recent developments in commodity futures markets, Brunetti and Reiffen (2011), Acharya, Lochstoer, and Ramadorai (forthcoming), Cheng, Kirilenko, and Xiong (2012), and Hamilton and Wu (forthcoming) proposed that the growing volume of commodity index investors could produce hedging price pressure on the buy side, with Hamilton and Wu (forthcoming) finding that the average compensation to the long position in oil futures contracts has decreased but become substantially more volatile since 2005. Etula (forthcoming), Acharya, Lochstoer, and Ramadorai (forthcoming), Danielsson, Shin, andZigrand (2011), andCheng, Kirilenko, andXiong (2012) have stressed the role of limited working capital on the part of potential arbitrageurs as the key factor determining how much the futures price might deviate from the expected future spot price.…”
Section: Aboutmentioning
confidence: 99%
“…Bessembinder, Carrion, Tuttle, and Venkataraman (2012) found price effects that were usually reversed within 15 minutes, while Stoll and Whaley (2010) found little impact of the roll. Brunetti and Reiffen (2011) reported that higher index-fund positions raised the return on the second versus the near contract during the roll periods, while Aulerich, Irwin, and Garcia (2013) found the opposite effect.…”
mentioning
confidence: 98%
“…Similar ideas were also addressed from different perspectives in Acharya et al (2013) and Brunetti and Reiffen (2014), who explored trading in futures markets and hedging costs. They developed equilibrium models in which speculators are liquidity providers to hedgers.…”
Section: Previous Studiesmentioning
confidence: 98%
“…These constraints would lead to limits to arbitrage between equity and commodity markets, which in turn would affect commodity futures prices and reduce hedging activity. Brunetti and Reiffen (2014) investigated whether trading by commodity index traders would affect the cost of hedging in commodity futures markets. Although they do not account for transaction costs explicitly, they do incorporate the idea that the volatility of futures prices impact hedging costs.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Among all documented effects of the financialization developed in Section 2.2.3, the price pressure generated by CITs around the roll could affect KRT findings. In particular, Brunetti and Reiffen (2014) document that CITs act as insurance suppliers. They modify the risk‐sharing structure in the postfinancialization and potentially insurance prices.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%